Sarcopenia in patients with chronic kidney disease - VELİOĞLU, ARZU; TUĞLULAR, ZÜBEYDE SERHAN (My University, 2022)
Sarcopenia is defined as a decrease in muscle mass and muscle strength, and its frequency increases with aging. Since different criteria and methods can be used for its definition, its incidence rates vary. Chronic kidney disease is a progressive process and many systems may be affected in these patients. Studies also show that chronic kidney disease can lead to the development of sarcopenia. Many factors are held responsible for the development of sarcopenia in chronic kidney disease. Age, inflammation, malnutrition, uremic toxins, and hormonal imbalance are the most important ones. In this review, general information about sarcopenia and the development of sarcopenia in patients with chronic kidney disease are discussed in light of the literature.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Urology; Chronic kidney disease; renal transplantation; sarcopenia; ELDERLY-PATIENTS; PREVALENCE; ASSOCIATION; Chronic kidney disease; renal transplantation; sarcopenia